3D LIDAR based on FPCB mirror. (April 2022) - Tai, Trevor S.; Zuo, Hui; He, Siyuan
Abstract: This paper presents the first 3D LIDAR (light detection and ranging) constructed from two 1D FPCB (flexible printed circuit board) oscillation mirrors and one single-point LIDAR with a very low total cost of ∼$150 (assuming no additional angle sensor used). One FPCB mirror is for vertical scanning and the other is for horizontal scanning. The low cost is realized because of the low cost 1D FPCB mirror (a few dollars), as well as the widely available and relatively easy to make single-point LIDAR (<$100 cost for mass production). The 3D LIDAR can be used to obtain 3D map for navigation and obstacle avoidance of AGVs (automated guidance vehicles) subject to low speed and low acceleration. The FPCB mirror in this paper evolves from FPCB micromirrors previously developed but has a large aperture (20 × 20 mm). The achieved performance is: horizontal and vertical FOV (field of view) of 38° and 24°, respectively, 12.5 or 25 horizontal scanning lines, refreshing rate of 2, 4 or 8 fps (frames per second), 0.2∼20 m detection distance for low reflectivity object, and 1, 250∼5, 000 points/frame when using the standard single-point LIDAR (TF03). If using a customized single-point LIDAR, the distance would be increased to 50∼80 m with 10 times more points/frame. The 3D LIDAR is suitable for AGV's navigation and obstacle avoidance. Modeling, prototyping and testing are presented.